(untitled) (Journal of Geography and Environmental Management, 2018)
The article deals with the experience of using satellite methods of determining coordinates based on measurements performed by global navigation satellite systems (GLONASS, GPS, etc.), fundamentally changing the technology and accuracy of geodetic measurements. For topographic and geodetic production, it is important to establish a connection between the system of geodetic heights obtained from satellite leveling, with a system of normal heights derived from surface geometric leveling. The relationship between geodetic and normal heights is realized through an anomaly of height (the height of a quasi-geoid), which can be calculated from the results of gravimetric measurements performed on the surface of the Earth or related to its surface. Accurate definition of the height anomaly allows using satellite leveling instead of labor-intensive ground leveling. The problem of determining the gravimetric deviations of the plumb line is also urgent; Characteristic of the deviation of the real gravitational field of the Earth from the normal. Components of the plumb deflections are used in solving the reduction problems of higher geodesy, in establishing the connection between astronomical and geodetic coordinate systems, etc. Classical methods for determining transformants of the gravitational field, based on integral formulas, do not take into account that the initial information is discrete, burdened by measurement errors and is not known on the entire surface of the Earth. An important requirement of today is a theoretical and practical solution to the problem of determining the transformants of the gravitational field in real time.